Znaczenie starodrzewu dla zachowania różnorodności porostów w lasach na przykładzie pozostałości Puszczy Mazowieckiej - Kubiak, Dariusz (Leśne Prace Badawcze, 2013)
The paper presents the results of a lichenological study conducted in 2012 in the 'Lekowo’ forest complex, situated in the north-western part of Mazovia (Forest Division of Ciechanów). It is the largest forest complex in the area, covering 1596 ha. The research area comprises two small nature reserves (’Lekowo’ – 5.31 ha, and 'Modła’ – 9.36 ha) with old-growth oak trees (160–200 years of age) and adjacent managed pine forests (76-107 years of age). The aim of this study was to investigate the species composition of the lichen biota in both reserves and to determine the role of nature reserves in preserving lichen diversity. Results of the study showed that old-growth stands, in particular those composed of oak trees above recommended felling age, provide habitats for a large group of stenotopic forest lichens which are absent in managed forests. The 'Lekowo’ and 'Modła’ nature reserves, despite their small areas, are valuable refuges that help to conserve remarkable lichen diversity at the local scale, and serve as potential diaspore sources for many rare and threatened lichen species.